Recession Vs Myotomy–Comparative Analysis of Two Surgical Procedures of Weakening Inferior Oblique Muscle Overaction - Alajbegovic-Halimic, Jasmina (Med Arch, 2015)
INTRODUCTION: Inferior oblique overaction (IOOA) can be primary or secondary, isolated or combined to other types of horizontal deviation, mostly with esotropias. Surgical weakening of IOOA means several techniques like; recession, myotomy, myectomy, anteroposition etc. GOALS: we analyzed the effect of inferior oblique muscle surgical weakening comparing two groups of patients with primary hypertropia. MATERIAL AND METHODS: In 5-years retrospective study, we observed 33 patients on which we did the surgical procedure of weakening inferior muscle overaction by two methods; recession and myotomy. RESULTS: In total number of 33 patients, there were 57,6% male and 42,4% female patients with average age of 10,6±7,5 (in range of 4–36). There was 33,3% of isolated primary hypertropias, and 66,7% combined with esotropias. At 23 (69,9%) patients the recession surgical procedure was done, and with 10 (30,1%) myotomy. Better effect and binocularity was in 65,2% of patients in recession group which was statistically significant with significance level of p<0,0, χ2=5,705; p=0,021. CONCLUSION: Comparing of two surgical procedures of weakening inferior oblique muscles overaction, recession is better procedure than myotomy.